Spinel-group minerals as a record of magmatic and metamorphic processes: evidence from the highly altered Morro do Onça ultramafic suite, São Francisco Craton (Brazil) - Guice, George L.; Magalhães, Joana Reis; Pinheiro, Marco Aurélio Piacentini; Ferreira, Raianny Carolini Ramos; Meira, Vinícius Tieppo; Melo-Silva, Paola; Ackerson, Michael R. (Contributions to mineralogy and petrology, 2022)
The Morro do Onça suite is a package of ultramafic rocks in the southern São Francisco Craton, Brazil. Owing to the complete alteration of primary silicate minerals, the Morro do Onça suite has been the subject of diverging interpretations, including: part of a retrogressed eclogite-facies Paleoproterozoic ophiolite/accretionary wedge or an Archean komatiite flow(s). In this paper, we utilize spinel-group mineral chemistry—alongside field mapping, petrography, silicate mineral chemistry and bulk-rock geochemistry—to decipher the magmatic and metamorphic evolution of the Morro do Onça suite. A komatiite origin is supported by the identification of spinifex-textured layers, as well as primary spinel-group mineral compositions (mean Cr-number = 79; mean TiO 2 = 0.3 wt%) and chondrite-normalized bulk-rock rare-earth element values ([Sm–Lu] N = 1.2–5.1). Metamorphism reached mid/upper amphibolite-facies and was likely responsible for Al mobility on mineral and bulk-rock scales, demonstrating that the bulk-rock Al/Ti proxy commonly used to classify komatiites is susceptible to alteration. Thus, the Morro do Onça komatiites record variable bulk-rock Al/Ti values (17–47) that overlap with both Munro- (Al/Ti = 22) and Weltevreden-type (Al/Ti = 30) komatiites. Based on immobile trace-element ratios ([Gd/Lu] N = 0.6–2.0) and primary spinel-group mineral compositions, we classify the Morro do Onça komatiites as Weltevreden-type. Mesoarchean komatiites related to mantle plume-magmatism are now recognized throughout the southern São Francisco Craton, potentially suggesting that its precursor lithosphere was continuous during this Era.